The role of oyster shell extract as a stimulant of sperm motility for patients with secondary infertility (asthenospermia) and diabetes (type II) before and after in vitro preparation for IUI - Othman Hashem Mohammed; Rania Sabri Hasan (Zien Journals, 2024)
Diabetes mellitus diabetes mellitus the most common diseases that present in many infertile patients. This study was conducted to overwhelm the negative response for the diabetes semen by in vitro activation techniques using a medium containing motility stimulants (i.e oyster). The medium used for in vitro activation was Hams F12 with 0.5% (oyster ) and two techniques were performed namely; wash and spin technique and density gradient technique. The results showed that the mean of sperm motility (grade A and grade B ) after activation by using density gradient technique with medium containing 0.5% (oyster) was significantly (P <0.001) higher than that of before activation and after activation by using wash and spin technique. According to the data of the present study, the best results of sperm motility were noticed when using a medium containing 0.5% (oyster) with density gradient technique for diabetic men. This data can be utilized to enhance the output of diabetic type 2 patient through assisted reproductive technologies programs>
Keywords: Diabetes mellitus; Density gradient washing technique; Oyster